Anisotropic thermal conductivities and structure in lignin-based microscale carbon fibers. (June 2019) - Wang, Ridong; Zobeiri, Hamidreza; Lin, Huan; Qu, Wangda; Bai, Xianglan; Deng, Cheng; Wang, Xinwei
Abstract: It is very important to know whether the thermal conductivity of carbon fibers in the directions of fiber axis (axial thermal conductivity, κ a ) and fiber radius (radial thermal conductivity, κ r ) are anisotropic. Relevant measurement is strongly hindered by microsize of carbon fibers in the radial direction. In this work, a novel method by combining frequency domain energy transport state-resolved Raman and transient electrothermal techniques is developed to overcome this drawback to achieve thermal conductivity anisotropy study of lignin-based microscale carbon fibers. Four fibers are characterized and the difference of κ a among them is very small, and κ a is around 1.8 W m −1  K −1 while the difference of κ r is very large. The κ r varies from 0.11 to 8.0 W m −1  K −1, revealing strong structure anisotropy and radial structure variation. The thermal conductivity variation against temperature also shows very different behavior. κ a features a reduction of more than one order of magnitude from room temperature to 10.4 K while κ r shows very little change from room temperature to 77 K. For the same carbon fiber, there is also a large difference of κ r at different axial positions. Detailed Raman study of the axial and radial structures uncovers very strong structure anisotropy and explains the observed anisotropic thermal conductivities. Graphical abstract: Image 1